Free Inquiry Learning Model with Experimental Methods on The Learning Outcomes of Class X Students of Senior High School on The Subject of Motion - Sari, R S; Ningsi, N; Nasarudin, N; Hakim, A R (Department of Physics, Faculty of Mathematics and Natural Sciences, 2022)
The number of students who complain about the difficulty of learning physics is due to the many formulas and calculations so that the teachers always vary their teaching methods so that the material taught can be absorbed by students through this research, which is expected to overcome these problems. In addition, this study also aims to see the effect of applying the free inquiry learning model with the experimental method on student learning outcomes. This research procedure uses a quasi-experimental method. The sample in this study were all students of SMAN 1 Kolaka in class X which consisted of 10 classes totaling 400 people. In testing the pre-test data, the first ability of students in both classes is the same. After learning motion material in the experimental class with the Free Inquiry Learning Model with the experimental method, and the control class with the experimental method, the post-test data obtained with the experimental class average value being higher than the control class. The test results show that the free inquiry learning model on student learning outcomes in motion subjects can significantly improve student learning outcomes.